Improving proton conductivity of metal organic framework materials by reducing crystallinity. (16th June 2022) - Tang, Huan; Lv, Xueyi; Du, Juan; Liu, Yang; Liu, Jie; Guo, Lihua; Zheng, Xiaofeng; Hao, Hongguo; Liu, Zhe
Abstract: Developing a new type of proton conductive material is key to improve the energy conversion performance of proton exchange membrane fuel cell (PEMFC). In recent years, metal organic framework (MOF) matrix conductive materials have become one of the research hotspots in the field of MOF. However, the grain boundaries in MOF particles and MOF@polymer composite films make it difficult to form long‐range ordered proton transport channels. Reducing crystallinity and changing the internal structural properties of MOF matrix may effectively improve its proton conductivity. In this study, some synthesis strategies were used to induce the crystallinity of MOF matrix to improve the proton conductivity, and low‐crystallinity MOG materials were obtained. In all, eight materials were prepared. The morphology characterization and proton conductivity of MOF and MOG materials were studied to explore the influence of different crystallinities and internal structures on proton conductivity. The results explicitly indicated that for the hydrophilic materials, the proton conductivity of MOG‐MOF‐808, MOG‐UiO‐66, MOG‐HKUST‐1 was significantly improved, compared with the corresponding MOFs at 75% RH. Among them, MOG‐MOF‐808 and MOG‐UiO‐66 show strong water stability and thermal stability, ensuring that it can be applied in special and complex environments. For the hydrophobic ZIF‐8 and MOG‐ZIF‐8, both their proton conductivities are low due to the material characteristics and network structures, while the proton conductivity of MOG‐ZIF‐8 is also higher than that of ZIF‐8 at 303 K. The results show that the abundant low‐crystallinity network structure in MOG materials played a very important role in improving the proton conductivity of the hydrophilic materials. Abstract : The abundant weakly crystalline network structure in MOG materials has a positive effect on improving the proton conductivity of the materials. In particular, the proton conductivities of MOG‐MOF‐808 and MOG‐UiO‐66 reach 3.06 × 10 −2 and 1.23 × 10 −2  S·cm −1 at 353 K and 75% RH, respectively. Compared with the conventional MOF materials, increasing the proton conductivity of MOF materials by reducing the crystallinity provides a new idea for the design and tuning of the proton conductivity of MOF materials. Highlights: MOG materials have higher proton conductivity than MOFs at 75% RH. At 303 K, the conductivity of MOG‐MOF‐808 (1.35×10 −2  S·cm −1 ) increased 196% relative to MOF‐808, and MOG‐UiO‐66 (3.89×10 −3  S·cm −1 ) is about 73 times that of UiO‐66. The three‐dimensional MOG structure has a coherent three‐dimensional hydrogen bonding network, which can provide long‐range ordered proton transfer channels and enhance proton transfer efficiency. Improving proton conductivity of MOF materials by reducing crystallinity provided a new idea for the design and adjustment of proton conductivity of MOF materials.